Analisis Nasikh Wa Mansukh Hadis tentang Menyimpan Daging Kurban Lebih dari Tiga Hari - Sely Agustin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Hadith studies are an important discipline in understanding the dynamics of Islamic law. One interesting topic to explore is the concept of nasikh wa mansukh, which refers to a hadith that cancels or replaces the ruling of a previous hadith. This study focuses on the hadith concerning the prohibition of storing sacrificial meat for more than three days, which in the early days of Islam was enforced to encourage the distribution of meat to the poor. This prohibition was later abrogated by another hadith that allowed the storage of sacrificial meat for a longer period of time as needed. The research method used was a literature study with a descriptive-analytical approach to hadith literature, sharah books, and the works of classical and contemporary scholars. The results of the study show that this change in law reflects the flexibility of Sharia in responding to the social conditions of the ummah, as well as emphasizing the principles of maslahat and social concern as the basis of Islamic law. This study is expected to contribute to enriching the understanding of Muslims regarding the concept of nasikh wa mansukh in hadith, while also emphasizing the relevance of the teachings of the Prophet in the context of modern life.